Charismatic pentecostalism: an urban religious response to Zimbabwe’s political and economic meltdown. the case of United Family International Church (U.F.I.C), Harare Metropolitan province. - Yesaya, Priviledge (Midlands State University, 2018)
The study was carried out in Harare Metropolitan Province focusing particularly on the United Family International Church (UFIC). The study sought to understand, with particular reference to U.F.I.C, the rise of Charismatic Pentecostalism in the face of harsh political and economic conditions facing Zimbabwe. The study made use of mixed method research a methodology which includes the integration of the qualitative and quantitative research methods as the main research methodology. The findings suggest that there is an interconnection between the emergence of charismatic Pentecostalism and Zimbabwe’s economic and political meltdown as evidenced by the emergence of this phenomenon during a political and economic unstable environment. Further, the study has also established that charismatic Pentecostalism in Zimbabwe seems to be serving the interest of those at the top of the social ladder and thus becoming an instrument of capitalism. The study hence projects a decline of charismatic Pentecostalism in case of Zimbabwe’s economic and political fortunes. The secularization theory has also been used to further exemplify how religion can simply lose its significance at the advancement of science, rationality and technology. As such, the study has established that Charismatic Pentecostalism in Zimbabwe is a passing phase.